Skin lesions in systemic lupus erythematosus. Part 2: clinical and histological features - A. A. Shumilova; E. I. Travkina; T. M. Reshetnyak (Современная ревматология, 2022)
Skin lesions in systemic lupus erythematosus (SLE) are not just a cosmetic defect, accompanied by a deterioration in the quality of life and psychological discomfort, but, possibly, the first sign of a systemic course of disease. Systemic involvement can develop in patients with almost any type of cutaneous lupus erythematosus (CLE), requiring the study of CLE in combination with SLE. Dermatologists are the first to face with skin manifestations of SLE, while other organs and systems affection leads the patient to a rheumatologist. It is important to understand that skin lesions do not cause irreversible organ damage, but continuity of therapeutic approaches between a dermatologist and a rheumatologist is necessary. The review presents the clinical signs, diagnostic features and histological characteristics of CLE.